Effects of dietary fat source on beef quality - Ribeiro, Felipe Azevedo (2017)
Feeding high levels of distillers grains increases polyunsaturated fatty acid (PUFA) levels in beef. It is well stablished that beef with higher concentrations of PUFA is more likely to have increased lipid and myoglobin oxidation. This is important because lipid and myoglobin oxidation lead to off-flavor development and discoloration of retail-displayed beef, reducing display life. In the first study, the effects of feeding different dietary fat sources with modified distillers grains plus solubles (MDGS) on beef display life were evaluated. Results suggest that feeding MDGS to cattle reduces color and lipid stability in addition to increasing C18:2 and PUFA content of beef in comparison to the corn diet. Thus, feeding MDGS to cattle has the potential to reduce beef display life. Perhaps, MDGS in feedlot diets increases PUFA concentration in the sarcoplasmic reticulum (SR) membrane, thereby altering membrane integrity, resulting in more rapid calcium leakage and improved tenderness. Therefore, the second study was dedicated to evaluate the effects of dietary fat source on the basic mechanism of beef tenderization. Feeding MDGS to cattle increased 18:2 and tended to increase PUFA concentration in the SR membrane, in addition to increase free calcium at d 2 postmortem in comparison to the corn diet. Beef from cattle finished on de-oiled MDGS and de-oiled MDGS plus oil had lower Warner-Bratzler shear force values than beef from cattle finished on corn at 2 d postmortem. No differences among dietary treatments were found for sarcomere length and troponin T degradation at 2 d postmortem. The results from this study suggest that feeding MDGS may increase tenderness, possibly by increasing free calcium in muscle early post-mortem. However, the true mechanism by which dietary fat source may accelerate the beef tenderization process is still unclear and should be further explored.